2018
DOI: 10.29312/remexca.v3i3.1448
|View full text |Cite
|
Sign up to set email alerts
|

El CaCl2 en la vida florero de gerbera: pigmentos, fenoles, lignina y anatomía del escapo*

Abstract: Gerbera jamesonii presenta una vida florero corta caracterizada por el doblado del tallo floral (escapo). Con el objetivo de alargar la vida f lorero de gerbera se probaron tres concentraciones de CaCl2 (0.1, 0.5 y 1.0%) en las variedades Duela y Shirlaine. Las concentraciones 0.5% y 1.0% redujeron la pérdida de peso de la f lor entera y lígulas en comparación con el testigo. La concentración 0.5% fue el mejor tratamiento, aumentó la vida media florero (25 d Duela y 24 d Shirlaine). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…Nevertheless, it has been noted in another study that gerbera in hydroponics absorbs more water at a high concentration of Ca-nano chelate at 3 g L −1, and the diameter of the flower heads begins to reduce in parallel with increased water consumption because of the ligules' dehydration [ 80 ]. Researchers discovered that floral stems given CaCl 2 and CaO-NPs at 150 mg L −1 maintained a weight loss of less than 6% before the 15th day of storage, demonstrating a beneficial role for CaO-NP in preserving gerbera flowers for a longer period and delaying the signs of aging or senescence [ 81 ]. CaO-NPs at 150 mgL −1 decreased stem bending and weight loss, improving the quality of gerbera flowers [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been noted in another study that gerbera in hydroponics absorbs more water at a high concentration of Ca-nano chelate at 3 g L −1, and the diameter of the flower heads begins to reduce in parallel with increased water consumption because of the ligules' dehydration [ 80 ]. Researchers discovered that floral stems given CaCl 2 and CaO-NPs at 150 mg L −1 maintained a weight loss of less than 6% before the 15th day of storage, demonstrating a beneficial role for CaO-NP in preserving gerbera flowers for a longer period and delaying the signs of aging or senescence [ 81 ]. CaO-NPs at 150 mgL −1 decreased stem bending and weight loss, improving the quality of gerbera flowers [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…the type of cultivar, agronomic conditions, stage of maturity, as well as management and postharvest treatments to which they are subjected. González-Aguilar and Zavaleta-Mancera (2012) reported that the application of CaCl 2 to the vase solution of two varieties of gerbera promoted the accumulation of phenols and delayed senescence.…”
Section: Total Antioxidant Capacity and Total Phenolic Contentmentioning
confidence: 99%
“…Het knikken van de steel tijdens het vaasleven is uitgebreid onderzocht en gedocumenteerd (Dubuc-Lebreux en Viet, 1985;Marousky, 1986;Perik et al, 2012;González-Aguilar, 2012 In Bijlage 8 zijn de resultaten van deze metingen per tijdstip, ras en behandeling in detail weergegeven, en in dit hoofdstuk vatten we ze samen.…”
Section: Figuur 44 Stelen Rich En Pre-semmy Geoogst Op 2 Mei Knikten unclassified